A cluster-randomised, controlled proof-of-concept study to explore the feasibility and effect of a patient-directed intervention on quality of life in patients with advanced soft tissue sarcoma. Issue 6 (30th June 2017) - Schuler, Markus; Richter, Stephan; Ehninger, Gerhard; Bornhäuser, Martin; Hentschel, Leopold
Abstract : Introduction: Even with evolving and expanding therapeutical options for the treatment of advanced sarcomas over recent years, the balance between efficacy and toxicity still remains a major concern. Moreover, the symptom burden in patients with sarcoma remains high compared with other malignant diseases. It is, therefore, crucial to assess treatment effectiveness not only in terms of disease-related outcomes (eg, overall survival) but also from an individual and patient-centred perspective using the assessment of patient-reported outcomes (PROs). By focusing on PROs as a primary study endpoint, we aim to address key issues for patients with advanced soft tissue sarcoma (STS) undergoing palliative treatment. Methods and analysis: The protocol of the YonLife study describes a multicentre, cluster-randomised, controlled, open-label proof-of-concept study conducted in patients with advanced or metastatic STS treated with trabectedin in seven German hospitals. The primary objective of the study is to exploratively compare overall quality of life between the patients receiving a multidimensional intervention based on individual PROs and those receiving usual supportive treatment. This complex intervention consists of the (1) electronic assessment of PRO, (2) creation of a case vignette based on PRO and clinical data and (3) treatment suggestions based on the discussion of these vignettes in a regularly meeting expert panel. Additionally, the YonLife trial assesses the applicability of a tablet-based assessment of PROs. Patients' and physicians' acceptance and challenges concerning the implementation process will be evaluated. Ethics and dissemination: The YonLife trial has been approved by the Ethics Committee of the University Hospital Dresden as well as by the relevant institutions of each participating centre before patient enrolment. The findings will be reported via relevant peer-reviewed journals as well as through presentation at international conferences. Trial registration number: NCT02204111, pre-results.